The effects of various TPNR binder compositions on feedstock preparation for MIM process - Hassan, Norita; Ahmad, Sahrim; Muhamad, Norhamidi; Omar, Mohd Afian; Hassan, Noor Azlina (Trans Tech Publications, Switzerland, 2015)
Metal injection moulding (MIM) feedstock is a mixture of metal powder and binder. The function of the binder system is to provide flow ability of the metal particles and shape retention of the moulded parts. The behaviour of the feedstock depends greatly on the binder formulations and its composition. In these studies, the possibility of using thermoplastic natural rubber (TPNR) as a binder system has been preliminarily investigated. The TPNR binder containing of natural rubber (NR) and polyethylene (PE) were studied at variable compositions. The characterization includes of mixing parameter, mixing torque and SEM micrograph of TPNR. Results show that the optimumcomposition of NR is about 40% in volume fraction of TPNR binder. The rheological results of the feedstock are considered to be used in MIM process as bio-composite binder.